Staff Low Back Injury Risk During Assisted Falls Virtual Reality Simulations. (June 2023) - Broderick, Vianna; Barrett, Blake; Phillips, Samuel; Cowan, Linda; Friedman, Yvonne; McKinney, Andrea; Chavez, Margeaux; Lind, Jason; Bradley, Sarah; Kaplan, Howard; Bulat, Tatjana
Background: Assisted falls occur when staff try to minimize the impact of falls by slowing a patient's descent. Assisting a patient fall may decrease patient injury risk, but biomechanical risk of injury to staff has not been evaluated. Assisted falls virtual reality (VR) simulations were conducted to examine staff low back injury risk during common assisted falls scenarios. Methods: VR simulations of a toilet to wheelchair transfer were developed with a male patient avatar for three assisted falls scenarios: standing up from toilet, sitting down on wheelchair, and ambulation. Patient avatar weight was modified to reflect normal, underweight, and overweight adult patients. The average spinal compression force at L5/S1 was calculated for each participant with five trials per three scenarios while utilizing physical ergonomic techniques and compared to the safe spinal compression limit of 3, 400 Newtons (N). Findings: Six staff participants completed 90 VR simulations in total. The average calculated spinal compression force ranged from 7, 132 N to 27, 901 N. All participant trials exceeded the safe spinal compression limit of 3, 400 N for every assisted falls scenario and avatar weight despite application of ergonomic techniques including wide stance, knees bent, and backs straight. Conclusions/Application to Practice: Staff are at risk for low back injury if they assist falls regardless of the adult patient weight and application of ergonomic techniques. Safer alternatives like the implementation of mobility screening tools and safe patient handling and mobility technology are needed to help prevent assisted falls to decrease injury risk to both patients and staff.